Rancang Bangun Aplikasi Visualisasi Dan Administrasi Manajemen Parkir Pada Suatu Pusat Perbelanjaan - Ardhana, Faizal; Sukmaaji, Anjik; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
To solve the problems listed above made ??an application that is able to provide the certainty of an empty parking lot, parking information looking for how many locations are available and time is not run out useless because of looking for parking locations and thus can save the use of fuel other than that with a system that this made ??will reduce the level of customer disappointed for not getting the location of parking.